The positive impact of structured teaching in the operating room. (19th August 2015) - Leung, Yee; Salfinger, Stuart; Mercer, Annette
Abstract : Background: A survey of obstetric and gynaecology trainees in Australia found the trainee's opinion of the consultants' teaching ability for laparoscopic procedures and procedures dealing with complications as 'poor' in 21.2% and 23.4% of responses, respectively (Aust NZ J Obstet Gynaecol 2009; 49: 84). Surgical caseload per trainee is falling for a variety of reasons. Strategies need to be adopted to enhance the surgical learning experience of trainees in the operating room. Aims: We describe the use of a structured encounter template to facilitate the teaching of surgery in the operating room and report the response of the trainees to this intervention. Methods: Trainees attached to a gynaecologic surgery unit all underwent surgical training using a set format based on the surgical encounter template, including briefing, goal setting and intra‐operative teaching aims as well as debriefing. Data on the trainees' experience and perception of their learning experience were then collected and analysed as quantitative and qualitative data sets. Results: The trainees reported satisfaction with the use of a structured encounter template to facilitate the surgical teaching in the operating room. Some trainees had not received such clarity of feedback or the opportunity to complete a procedure independently prior to using the structured encounter template. Conclusions: A structured surgical encounter template based on andragogy principles to focus consultant teaching in the operating room is highly acceptable to obstetric and gynaecology trainees in Australia. Allowing the trainee the opportunity to set objectives and receive feedback empowers the trainee and enhances their educational experience.